2024
DOI: 10.1021/acs.jmedchem.3c01361
|View full text |Cite
|
Sign up to set email alerts
|

Rising Star in Immunotherapy: Development and Therapeutic Potential of Small-Molecule Inhibitors Targeting Casitas B Cell Lymphoma-b (Cbl-b)

Lixin Zhou,
Jiamei Yang,
Kuojun Zhang
et al.

Abstract: Casitas B cell lymphoma-b (Cbl-b) is a vital negative regulator of TCR and BCR signaling pathways, playing a significant role in setting an appropriate threshold for the activation of T cells and controlling the tolerance of peripheral T cells via a variety of mechanisms. Overexpression of Cbl-b leads to immune hyporesponsiveness of T cells. Conversely, the deficiency of Cbl-b in T cells results in markedly increased production of IL-2, even in the lack of CD28 costimulation in vitro. And Cbl-b −/− mice sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Therefore, additional CI agents, especially those with a distinctive mechanism of action from checkpoint blockade, are urgently needed to improve the response rates and broaden indications to help more cancer patients . Toward this goal, we were interested in targeting Casitas B-lineage lymphoma proto-oncogene-b (Cbl-b), a RING E3 ligase, which acts as a negative regulator of T cell activation. For example, it has been shown that in mouse, knockout of Cbl-b, as well as knock-in of a functionally inactive Cbl-b (C373A) mutant, leads to hyperactivation of T cells and spontaneous rejection of tumor. A complicating factor is that in mammals, Cbl-b belongs to the Cbl family with two additional members: c-Cbl and Cbl-3. , The three members share a highly conserved N-terminus, including TKB and RING finger domains, while the C-terminus is more diverse, particularly for Cbl-3, which contains a significantly truncated C-terminus. In light of the high sequence and structural homology between Cbl-b and c-Cbl in the N-terminus, it was not readily clear to us how to achieve selectivity for Cbl-b over c-Cbl.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional CI agents, especially those with a distinctive mechanism of action from checkpoint blockade, are urgently needed to improve the response rates and broaden indications to help more cancer patients . Toward this goal, we were interested in targeting Casitas B-lineage lymphoma proto-oncogene-b (Cbl-b), a RING E3 ligase, which acts as a negative regulator of T cell activation. For example, it has been shown that in mouse, knockout of Cbl-b, as well as knock-in of a functionally inactive Cbl-b (C373A) mutant, leads to hyperactivation of T cells and spontaneous rejection of tumor. A complicating factor is that in mammals, Cbl-b belongs to the Cbl family with two additional members: c-Cbl and Cbl-3. , The three members share a highly conserved N-terminus, including TKB and RING finger domains, while the C-terminus is more diverse, particularly for Cbl-3, which contains a significantly truncated C-terminus. In light of the high sequence and structural homology between Cbl-b and c-Cbl in the N-terminus, it was not readily clear to us how to achieve selectivity for Cbl-b over c-Cbl.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies hypothesized that selective CBL-B inhibition over C-CBL is the key in solid tumor treatment. , However, high similarities in the sequence and structure of CBL-B and C-CBL make the design of selective CBL-B inhibitors a daunting challenge. ,,, CBL-B and C-CBL share high sequence homology in tyrosine kinase binding (TKB), LHR, and RING domain. ,, A study identified a few amino acids difference in the linker region between the N-terminal TKB domain and the C-terminal RING finger domain with 86% amino acid identity of CBL-B and C-CBL, respectively. , Therefore, how to exploit the little structural and sequence differences and their subtle dynamic and kinetic differences will be crucial to achieve selectivity. The binding affinities ( K d values) of known CBL-B inhibitors range from low-micromolar to nanomolar depending on assay conditions . There are a few k off values (dissociation rates) of CBL-B inhibitors in the literature, which are key kinetic properties of inhibitors. , Exploiting the structural difference, coupled with kinetics via their different dissociation behavior and their unique interaction along the dissociation pathways in CBL-B drug design, has not been well elaborated.…”
mentioning
confidence: 99%